The role of board of commissioners and transparency in improving bank operational efficiency and profitability - Lutfi Lutfi; Meliza Silvy; Rr. Iramani (Journal of Economics, Business, and Accountancy Ventura, 2014)
Good corporate governance is a critical aspect in banking industries because the larg- est part of the source of funds is from public. Two of the important aspects of good corporate governance are the role of the board of commissioners and transparency. This study aimed to assess the effect of the implementation of good governance, which is proxied by the role of the board of commissioners and transparency of financial and non-financial condition, toward the operational efficiency and profitability of the na- tional commercial banks in Indonesia. This study uses data of thirty six banks for five years, from 2008 to 2012. Random effect panel data technique is used to analyze the data since this technique can increase the power of statistical analysis. The results shows that in terms of efficiency only board that functions well capable of improving the operational efficiency of the banks. As for profitability, both good board of commis- sioners and public transparency are capable of increasing the bank operational profit- ability in Indonesia.